L’agir collectif des encadrantes de la petite enfance dans les structures d’accueil - Christine Gautier-Chovelon (Éducation et Socialisation)
The official texts encourage the institutions of early childhood to be meeting places participation and exchange while becoming educational receptions. To answer it collective work is institutionalized. In their daily newspaper, the directors are confronted with difficulties of management of this collective and setting of visibility of their activities. However in situation, the professional ones show creativity while taking part in the re-creation of collectives. This exploratory study, carried out near thirty-four directors of crib and six persons in charge of a service early childhood, is interested in the way in which meet and amalgamation concretely in all early childhood the individual one and the collective. It makes it possible to consider the real activity of the directors of crib such as it could be described in their daily interactions with the hierarchy, the colleagues, the partners and the parents at the time as of festive activities. The setting from of visibility of this dynamics comes to question its recognition and the production of new less discriminating social reports.